Strengthening RPPA Villages Through Digital Literacy: Memperkuat Desa RPPA Melalui Literasi Digital - Siti Fitriana; Qristin Violinda; Nila Kusumaningtyas; Abdul Rohman (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2026)
The Women- and Child-Friendly Village Program (RPPA) is a government initiative to strengthen the protection of women and children through community empowerment. However, its implementation in Lemahireng Village, Bawen District, Semarang Regency has been constrained by limited digital literacy and educational media. This community service program aimed to enhance community capacity through digital literacy education as a violence prevention strategy while strengthening the implementation of the RPPA program. The program employed a Participatory Action Research (PAR) approach involving needs assessment, planning, training, mentoring, implementation, and monitoring and evaluation. The beneficiaries included the village government, BUMDes Margo Mukti, women's organizations (PKK), and the Children's Forum. The program improved participants' average knowledge scores from 53.3% to 89.5% and produced digital literacy modules, educational videos, digital posters, and digital marketing support for BUMDes. These outcomes contribute to the sustainable implementation of a digital literacy-based RPPA program.